Effects of Al, Y, and Zn Additions on the Microstructure and Mechanical Properties of Mg−3Li Alloy. Issue 8 (30th January 2022) - Li, Yang; Wang, Jiahao; Wu, Ruizhi; Wei, Zhen; Ji, Qing; Zhong, Feng; Zhang, Shun; Yang, Zhenzhao; Wang, Jiaxiu; Jin, Siyuan; Xu, Lin; Hou, Legan
Abstract : The influence of Al, Y, and Zn additions on the microstructure and mechanical properties of Mg−3Li alloy is investigated. It is revealed that Al and Y form the Al2 Y phase that can refine α‐Mg grains. Y and Zn form the 18R long‐period‐stacking‐ordered (LPSO) structure phase that can coordinate deformation. In addition, the formed SFs can hinder dislocation slip. However, the Mg24 Y5 phase weakens the grain boundaries. After solid solution at 520 °C, the Al2 Y phase and LPSO phase do not change. The Mg24 Y5 phase gradually disappears, SFs decrease, and the grain of the alloy grows. After subsequent hot rolling at 350 °C, the grains and LPSO phase are gradually elongated along the rolling direction, and the LPSO phase is twisted. SFs increase and the grain of the alloy is refined. In addition, MgY phase is precipitated inside the matrix. With the rolling reduction of 70%, the Mg−3Li−1Al−4Y−1Zn alloy possesses the ultimate tensile strength (UTS) and elongation (EL) values of 287 MPa and 5.2%. Abstract : The Al2Y, Mg24Y5 and 18R long‐period‐stacking‐ordered (LPSO) phases are formed by adding Al, Y and Zn elements to the Mg‐3Li alloy. After solid solution, the Mg24Y5 phase gradually disappears. After the subsequent hot rolling, the LPSO phase is twisted, the MgY phase is precipitated inside the matrix. The mechanical properties of alloy increase.